Early Change in Area Strain Detected by 3D Speckle Tracking Is Associated With Subsequent Cardiotoxicity in Patients Treated With Low Doses of Anthracyclines - Piveta, Rafael B.; Rodrigues, Ana Clara T.; Vieira, Marcelo L. C.; Fischer, Cláudio H.; Afonso, Tania R.; Daminello, Edgar; Cruz, Felipe M.; Galvão, Tatiana F. G.; Filho, Edgar B. L.; Katz, Marcelo; Morhy, Samira S. (Frontiers in Cardiovascular Medicine, 2022)
Objective To evaluate the prognostic impact of the parameters of myocardial deformation using three-dimensional speckle tracking echocardiography (3DSTE) in patients with breast cancer who underwent chemotherapy with low doses of anthracyclines. Background Chemotherapy-related cardiotoxicity has an important prognostic impact on cancer survivors. Three-dimensional STE has revealed more consistent data than two-dimensional techniques and may represent a more accurate tool in the evaluation of myocardial function in patients who underwent chemotherapy. Methods We evaluated patients with breast cancer who were treated with anthracyclines (associated or not with trastuzumab) in five stages: baseline, after cumulative doses of 120 and 240 mg/m2 of doxorubicin, and then, after 6 months and at least 1 year after anthracyclines. Ultrasensitive troponin I (US-TnI) and a standard echocardiography study were performed at each stage. We analyzed left ventricular ejection fraction (LVEF) by Simpson's method, two-dimensional speckle tracking (2DSTE) with longitudinal and radial strain values, and 3DSTE with longitudinal, radial, and circumferential strain as well as twist, torsion, rotation, and three-dimensional global area strain (3DGAS). Cardiotoxicity was defined as a decrease in LVEF by more than 10 percentage points to a value lower than 53%. Results We evaluated 51 female patients who were aged 50.6 ± 11 years. After the cumulative dose of 240 mg/m2 of doxorubicin, US-TnI was increased (>34 pg/ml) in 21 patients (45%, p > 0.001), LVEF remained unchanged (p = 0.178), while 2DSTE longitudinal strain was decreased (from −17.8% to −17.1%, p < 0.001) and 3DSTE detected changes in longitudinal, radial, circumferential, and area strain. After a lower cumulative dose of doxorubicin (120 mg/m2), 3DGAS (p < 0.001) was the only parameter that was changed. In the follow-up, 7 (13%) patients presented a decrease in LVEF. Three-dimensional GAS early changed to abnormal values was the only variable associated with a subsequent decrease in LVEF (definitive cardiotoxicity). Conclusion In patients with breast cancer, 3DSTE detected early changes in area strain after very low doses of doxorubicin. The 3DGAS early changed to abnormal values was associated with a subsequent decrease in LVEF, representing a promising technique to predict chemotherapy-induced cardiomyopathy.